Evaluation Of Nephrocurative And Antioxidant Effect Of Aqueous Extract Of Hygrophila Spinosa In Gentamicin-Induced Nephrotoxicity In Rats - K.J. BIBU,; A.D. JOY, (International Journal of Pharma and Bio Sciences, 2010)
Hyrophila spinosa (H. spinosa) is used in folk medicine for various ailments and its different pharmacological activities have been reported. The present study was aimed at the evaluation of the nephrocurative and antioxidant effects of aqueous extract of H. spinosa against gentamicin (GM)-induced nephrotoxicity. Male Sprague Dawley rats (200-250g) were treated with gentamicin at 80 mg/kg i.p. for eight days and starting from day 9, the rats were treated with 50 mg/kg p.o. and 250 mg/kg p.o. H. spinosa for remaining 22 days. Blood samples were taken for the estimation of serum creatinine and urea. At the end of the experiment, kidneys were used for the estimation of superoxide dismutase, lipid peroxidation, catalase, reduced glutathione and for conducting histopathological studies. Gentamicin at the dose used significantly (P<0.05) increased the serum creatinine, urea, lipid peroxidation levels and significantly (P<0.05) decreased superoxide dismutase, catalase and reduced glutathione levels. It also produced severe histological changes. H. spinosa at 250 mg/kg orally significantly (P<0.05) reduced the creatinine, urea and lipid peroxidation levels, increased superoxide dismutase, catalase, reduced glutathione levels and reversed the histopathological changes produced by GM administration. This effect was dose dependent and in conclusion, the study suggested that H. spinosa reduced GM-induced nephrotoxicity.